Ensayo de la fertilización con fosforo y potasio en el rendimiento de la Vid variedad Borgoña Negra (Isabella) en el distrito de San Antonio de Cumbaza San Martin - Ramirez Pinedo, Weninger (2002)
With the objective to find the appropriate doses of fertilizer in the wine yields and degree brix in the variety black borgoña the present work in the district of San Antonio, The conduction of the experiment was Black random to tally (B.C.A.) with factorial arrangement. Dose of fertilizers phosphorus and potassium were studied in wine in the following way, T1, (83,3 -16,66 - 41,65), T2 (83,3 - 16,66 - 124,95), T3 (83,3 - 16,66 - 208,25), T4 (83,3 - 49,98 - 41,65), T5 (83,3 - 49,98 - 124,95), T6 (83,3-49,98- 208,25), T7 (83,3 - 83,3 -41,65), T8 (83,3 - 83,3 - 124.95), T9 (83,3 - 83,3 - 208,25), T10 (83,3 - 00 - 00), to keep in mind the number of plants inside the experimental field, adding a total of 27 treatments. In the treatment a regulator of growth denominated hydrogenated cianamid was applied (Donmex) with the purpose of standarize and to activate the spront after the pruning. Seven applications was performed to control fungous diseases during the development from the wine to the 11, 14, 18, 23, 30, 37, 55, 70 days the ok using the chemical product Metalaxil + Mancozed to the dose of 60 g./20Lt. It was diluted mixed with an adherent to the dose of 10 ml./20Lt of water, this application avoided the presence of the flowering miidiu. The parameters that were evaluated were: Days to spronting, time of flowering, number of floral clusters, number of clotted clusters, weigh for cluster, cluster size, grain size, number of grains for cluster, weight of the grain, time to the crop, production for treatment, degree brix. With the obtained yields the related economic analysis B/C of each treatment was carried ant. The best yield as fertilizer in wine was obtained with the T2, with a yield of 3 805,55 Kg/Ha. And with a net value of 2 355,13 S/.